OPPORTUNITIES FOR SUSTAINABLE DEVELOPMENT OF LOGGING THROUGH OPTIMIZATION OF BUSINESS RELATIONS BETWEEN ECONOMIC SUBJECTS (Innovation in Woodworking Industry and Engineering design, 2026)
Wood has so far remained a major source of revenue that fund forest-cultural activities. It creates livelihood of populations in forest areas and improvement of its organization is in the interest of the state as a major forest owner and private timber companies and local communities. The present study has attempted comparative characteristic of economic results obtained by private logging companies. Different options has been discussed for improving relations between state and private forestry companies to achieve a lasting balance of interests in the allocation of income from logging under regulations established by the legislation, practical experience and advanced theoretical concepts in this area.